ADVANCES IN NONINVASIVE DRUG DELIVERY SYSTEMS OF OPIOIDS: FORMULATIONS AND CLINICAL PERSPECTIVE - Mundhey, Dhanashree A; Sapkal, Nidhi P; Daud, Anwar S (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Opioid continues as the main pharmacological treatment for severe acute pain. Extensive first-pass metabolism is the major limitation of opioid delivery by oral route. Thus, the parenteral route has been the only option for the delivery of opioids before the beginning of the 21 century. However, as the delivery through parenteral route is associated with limitation of being invasive, a strong need for developing non-invasive delivery systems has been felt among the drug delivery scientists. Since mucosal surfaces are rich in blood supply and provide rapid drug transport to the systemic circulation, this delivery system has been explored to enhance opioid bioavailability by avoiding their degradation through first-pass hepatic metabolism. Oral transmucosal delivery such as buccal and sublingual has progressed far beyond the use of traditional dosage forms developed with novel approaches emerging continuously. This review provides updated information about the use of opioids for the treatment of severe pain with special emphasis on the work done by various scientists on formulation development of opioid analgesics, especially by buccal and sublingual route for delivery of opioids along with their clinical perspective. Particular attention is given to new approaches enhancing bioavailability of opioids by these routes. Keywords: Opioids, Buccal, Oral drug, Sublingual delivery of opioids. st